Pengaruh Dividen Dari Investasi Saham Terhadap Minat Berinvestasi Mahasiswa Di Galeri Investasi Syariah IAIN Kerinci - Nurhikmah Nurhikmah; Tiara Tiara; Azhar Azhar (Journal Islamic Economic and Bussines Studies, 2022)
Millennials are currently participating in capital market stock investment activities, the Sharia Investment Gallery of IAIN Kerinci recorded the number of investors in 2020 as many as 573 with active investors up to 66 people or 11.5%. The purpose of this study was to determine the effect of dividend payments on student investment interest in the Syariah Investsai Gallery IAIN Kerinci. The population of this study amounted to 573 students who were registered as investors at GIS IAIN Kerinci with this number drawing a sample of 66 students by applying the purposive sampling technique by setting the criteria for active students to become investors. Simple linear regression was used as the analytical method. The results of this study conclude that dividends have no significant effect on student investment interest in the Sharia Investment Gallery of IAIN Kerinci.